2010
DOI: 10.1007/s00122-010-1479-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of salinity tolerance and analysis of allelic function of HvHKT1 and HvHKT2 in Tibetan wild barley

Abstract: Tibetan wild barley is rich in genetic diversity with potential allelic variation useful for salinity-tolerant improvement of the crop. The objectives of this study were to evaluate salinity tolerance and analysis of the allelic function of HvHKT1 and HvHKT2 in Tibetan wild barley. Salinity tolerance of 189 Tibetan wild barley accessions was evaluated in terms of reduced dry biomass under salinity stress. In addition, Na(+) and K(+) concentrations of 48 representative accessions differing in salinity tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 52 publications
5
96
0
Order By: Relevance
“…Six wild-barley accessions from the Near East were collected and previously characterized by Nevo et al (26)(27)(28). Six wild-barley genotypes were from the collection of Xu, since the 1960s, from the extensive area of the Tibetan Plateau (11,12), and evaluated by Dai et al (14,47) and Qiu et al (48). Among the cultivated barley genotypes used in this study, Padanggamu, Beiqing5, and Himala2 were hulless, also called qingke, and cultivated on the Tibetan Plateau and its vicinity.…”
Section: Methodsmentioning
confidence: 99%
“…Six wild-barley accessions from the Near East were collected and previously characterized by Nevo et al (26)(27)(28). Six wild-barley genotypes were from the collection of Xu, since the 1960s, from the extensive area of the Tibetan Plateau (11,12), and evaluated by Dai et al (14,47) and Qiu et al (48). Among the cultivated barley genotypes used in this study, Padanggamu, Beiqing5, and Himala2 were hulless, also called qingke, and cultivated on the Tibetan Plateau and its vicinity.…”
Section: Methodsmentioning
confidence: 99%
“…A study of 187 Tibetan wild barley (Hordeum vulgare L. ssp. spontaneum) accessions by Qiu et al (2011) showed a significant correlation (r = 0.455) between Na + accumulation and salt tolerance (% biomass after 27 days at 300 mM NaCl) but there were many accessions with the same Na + concentration and with different salt tolerance. A similar finding can be seen in the study by Chen et al (2005) for seven barley cultivars grown at 320 mM NaCl.…”
Section: Genetic Variation In Tissue Tolerance For the Purpose Of Plamentioning
confidence: 98%
“…An extraordinarily strong support for the importance of HKT-like proteins in mediating salinity stress tolerance has been provided by genetic and molecular studies in models (Sunarpi et al, 2005;Møller et al, 2009;Genc et al, 2010;Hauser and Horie, 2010;Plett et al, 2010;Qiu et al, 2011). In several cases, improved salinity tolerance has been associated with regions of genomes that included HKT-type transporters.…”
Section: Sodium Transport Systemsmentioning
confidence: 99%